Impact research of well layout schemes and fracture parameters on heat production performance of enhanced geothermal system considering water cooling effect. (15th September 2022) - Zheng, Jun; Li, Peng; Dou, Bin; Fan, Tao; Tian, Hong; Lai, Xiaotian
Abstract: The fluid flow route in an enhanced geothermal system (EGS) is jointly determined by well layout and fracture network, which affects the fluid flow and heat transmission process. To obtain an efficient EGS, it is critical to explore the best well layout and fracture parameter. In this study, combination effects of well layout scheme and fracturing networks are researched. A thermal-hydraulic-mechanical coupling model, accounting for the thermal shock impact of cool water on high temperature rock, is built to evaluate the heat production performance, which takes production temperature, production thermal power and reservoir recovery rate as indicators. Results indicate that addition of symmetrical injection wells could lengthen EGS's operating life and boost production thermal power. Connection between injection-production wells should be as close to the main direction of the fracture as possible to improve fluid flow rate, accelerate heat transfer, and increase heat recovery rate. Furthermore, Morris based sensitivity analyses are performed to identify the key variables influencing EGS production performance. It reveals that the most crucial parameters are injection pressure and fracture opening, which should be raised in practice as much as allowed on the assumption that the production temperature meets the threshold. Highlights: There is a strong coupling among reservoir temperature, thermal stress and permeability. Thermal shock of water cooling affects the rock fracture opening and permeability. Increasing injection wells symmetrically distributed can improve the EGS service life. Key elements of production performance are injection pressure and fracture opening.